2019
DOI: 10.1186/s12877-019-1070-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simple screening tool for caregiver grief in dementia caregiving

Abstract: Background Loss and grief are experienced by caregivers of persons with dementia (PWD), relating to the ambiguous loss of PWD even when they are still alive and the anticipation of future loss related to their physical death. Such experience of caregiver grief is not easily recognized in clinical practice, despite its association with adverse effects such as caregiver burden, caregiver depression and caregivers’ desire to place the PWD in nursing homes. We constructed a simple screening tool – bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In addition to evaluating effectiveness, research towards the development of accurate screening tools is required to ensure that healthcare providers are able to prescribe the appropriate intervention. 41 This scoping review also demonstrated how ongoing intervention research has engaged many groups of people connected to caregivers, including healthcare professionals. These interactions often occur when attempting to evaluate a certain intervention, as has been seen throughout the selected articles.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition to evaluating effectiveness, research towards the development of accurate screening tools is required to ensure that healthcare providers are able to prescribe the appropriate intervention. 41 This scoping review also demonstrated how ongoing intervention research has engaged many groups of people connected to caregivers, including healthcare professionals. These interactions often occur when attempting to evaluate a certain intervention, as has been seen throughout the selected articles.…”
Section: Discussionmentioning
confidence: 89%
“… 30 Caregiver grief may be challenging to recognize in clinical practice, and may not be frequently recognized by typical burden scales. 41 Previous work has identified difficulties in differentiating depressive symptoms from grief. 42 This highlights the importance of accurately diagnosing grief in informal caregivers, so that healthcare professionals are able to prescribe the appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the articles were led by the same first author and described caregiver grief as anticipation of future losses related to physical death of a person with dementia. 95,97,99 Marwit and Meuser 103 discussed caregiver grief as a stage-determined, internally consistent construct that is measurable but did not provide an explicit definition. Guerrero 71 defined caregiver grief as feelings of grief, including sadness, longing, worry, felt isolation, personal sacrifice, and burden prior to the death of the care recipient.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the sense of safety and security is shaken, the sense of continuity is disturbed, whereas the future seems uncertain [6]. According to recent findings, caregivers, at the time of diagnosis, experience sudden changes in their relationships and family structure, whereas they anticipate an uncertain future [7][8][9][10]. Moreover, during caregiving, caregivers often report high levels of stress, low self-esteem, low sense of well-being, depressive symptomatology, increased levels of burden, compromised physical Submit your Manuscript | www.austinpublishinggroup.com social and emotional support received [21].…”
Section: Introductionmentioning
confidence: 99%